Direct action antivirals are effective in the total eradication of HCV in renal transplants - Teresa Olea; Inmaculada Castillo; Carlos Jiménez; Javier Bartolomé; María José Santana; JA Quiroga; Vicente Carreño; Rafael Selgas (Annals of Antivirals and Antiretrovirals - Peertechz Publications, 2019)
Introduction: The main objective of our study was to analyze the effectiveness of antiviral treatment (conventional or with direct-acting antivirals (DAA)) for total eradication of Hepatitis C Virus (HCV) in kidney transplant (KT) recipients. DAA are known drugs that are approved by FDA for clinical and preclinical investigations. The effi cacy was analyzed by testing for the presence of HCV- ribonucleic acid (RNA) in the pellets obtained after ultracentrifugation of follow-up plasma samples and in peripheral blood mononuclear cells (PBMC) from patients with HCV infection who had achieved a sustained virological response (SVR). The safety, and the renal and hepatic repercussions of the antiviral treatment were also evaluated.